Soil water retention curves by tensiometers for two soils from Alfenas, MG, Brazil - Sarvasi, Flávio de Oliveira Cunha; Vieira, Sidney Rosa; de Castro, Orlando Melo; Barbosa, Conceição Correa (Pesquisa Agropecuaria Brasileira, 1992)
A method which uses 10 mm diameter porous capsules installed in rings containing soil cores was tested for its efficiency and practicability in the determination of soil retention curves. The tensiometer, the soil and the ring form a set which, when submetted to weighings and concomitant tensiometer readings provides the data pairs needed for the curves. The soils used are a Dark-Red Latossol with clay A horizon, and a Yellow. Red Podzolic with clay to medium A horizon, which are very distinct physically. The method used provided good results, is very fast, and yielded curves which agree with the physical condition of the soils, and with high correlation coefficients lo the model adjusted.